Mechanisms, Transmissions and Applications Proceedings of the Fourth MeTrApp Conference 2017 (Mechanisms and Machine Science,, 2018)
This volume contains the proceedings of MeTrApp 2017, the 4th Conference on Mechanisms, Transmissions and Applications, that was held in Trabzon, Turkey, July 3-5, 2017. The topics treated in this volume are Mechanism Design, Parallel Manipulators, Control Applications, Mechanical Transmissions, Cam Mechanisms, and Dynamics of Machinery. The conference was organised by the IFToMM Technical Committees for "Linkages and Mechanical Controls" and "Gearing and Transmissions" under the patronage of the IFToMM and sponsorship of Karadeniz Technical University, Izmir Institute of Technology and IFToMM Turkey (MAKTED). The aim of the conference was to bring together researchers, scientists, industry experts and students to provide, in a friendly and stimulating environment, the opportunity to exchange know-how and promote collaboration in the field of Mechanism and Machine Science. .